Development and characterization of poly(lactic-co-glycolic) acid nanoparticles loaded with copaiba oleoresin. (21st April 2018) - de Almeida Borges, Vinícius Raphael; Tavares, Marina R.; da Silva, Julianna Henriques; Tajber, Lidia; Boylan, Fabio; Ribeiro, Ana Ferreira; Nasciutti, Luiz Eurico; Cabral, Lucio Mendes; de Sousa, Valeria Pereira
Abstract: Copaiba oleoresin (CPO), obtained from Copaifera landgroffii, is described as active to a large number of diseases and more recently in the endometriosis treatment. In this work, poly(lactic-co-glycolic acid) (PLGA) nanoparticles containing CPO were obtained using the design of experiments (DOE) as a tool to optimize the production process. The nanoparticles optimized by means of DOE presented an activity in relation to the cellular viability of endometrial cells. The DOE showed that higher amounts of CPO combined with higher surfactant concentrations resulted in better encapsulation efficiency and size distribution along with good stability after freeze drying. The encapsulation efficiency was over 80% for all produced nanoparticles, which also presented sizes below 300 nm and spherical shape. A decrease in viability of endometrial stromal cells from ectopic endometrium of patients with endometriosis and from eutopic endometriotic lesions was demonstrated after 48 h of incubation with the CPO nanoparticles. The nanoparticles without CPO were not able to alter the cell viability of the same cells, indicating that this material was not cytotoxic to the tested cells and suggesting that the effect was specific to CPO. The results indicate that the use of CPO nanoparticles may represent a promising alternative for the treatment of endometriosis.